Muscle activity and kinematics show different responses to recurrent laryngeal nerve lesion in mammal swallowing - Gould, François D. H. (J Neurophysiol, 2020)
Understanding the interactions between neural and musculoskeletal systems is key to identifying mechanisms of functional failure. Mammalian swallowing is a complex, poorly understood motor process. Lesion of the recurrent laryngeal nerve, a sensory and motor nerve of the upper airway, results in airway protection failure (liquid entry into the airway) during swallowing through an unknown mechanism. We examined how muscle and kinematic changes after recurrent laryngeal nerve lesion relate to airway protection in eight infant pigs. We tested two hypotheses: 1) kinematics and muscle function will both change in response to lesion in swallows with and without airway protection failure, and 2) differences in both kinematics and muscle function will predict whether airway protection failure occurs in lesion and intact pigs. We recorded swallowing with high-speed videofluoroscopy and simultaneous electromyography of oropharyngeal muscles pre- and postrecurrent laryngeal nerve lesion. Lesion changed the relationship between airway protection and timing of tongue and hyoid movements. Changes in onset and duration of hyolaryngeal muscles postlesion were less associated with airway protection outcomes. The tongue and hyoid kinematics all predicted airway protection outcomes differently pre- and postlesion. Onset and duration of activity in only one infrahyoid and one suprahyoid muscle showed a change in predictive relationship pre- and postlesion. Kinematics of the tongue and hyoid more directly reflect changes in airway protections pre- and postlesion than muscle activation patterns. Identifying mechanisms of airway protection failure requires specific functional hypotheses that link neural motor outputs to muscle activation to specific movements. NEW & NOTEWORTHY Kinematic and muscle activity patterns of oropharyngeal structures used in swallowing show different patterns of response to lesion of the recurrent laryngeal nerve. Understanding how muscles act on structures to produce behavior is necessary to understand neural control.